2017
DOI: 10.1021/acs.biomac.6b01885
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Folate-Dendrimer-Coated Iron Oxide Theranostic Nanoparticles for Simultaneous Magnetic Resonance Imaging and Precise Cancer Cell Targeting

Abstract: The low therapeutic index of conventional chemotherapy and poor prognosis of patients diagnosed with metastatic cancers are prompting clinicians to adopt newer strategies to simultaneously detect cancer lesions at an early stage and to precisely deliver anticancer drugs to tumor sites. In this study, we employed a novel strategy to engineer a polyvalent theranostic nanocarrier consisting of superparamagnetic iron oxide nanoparticle core (SPIONs) decorated with folic acid-polyamidoamine dendrimers surface (FA-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 67 publications
0
67
0
Order By: Relevance
“…In figure 6a & b, we observed that FA-targeted micelle has higher cell uptake than the non-targeted formulation, which indirectly proves FR-mediated cell uptake. Previously, our lab has shown FR-competition experiment with various types of nanoparticles to prove the receptor mediated uptake [4446]. Herein, we used folic acid conjugated polymeric micelles, thus one can expect FA-SMA micelle will follow FR-mediated endocytosis and there will be FR-competition.…”
Section: Discussionmentioning
confidence: 99%
“…In figure 6a & b, we observed that FA-targeted micelle has higher cell uptake than the non-targeted formulation, which indirectly proves FR-mediated cell uptake. Previously, our lab has shown FR-competition experiment with various types of nanoparticles to prove the receptor mediated uptake [4446]. Herein, we used folic acid conjugated polymeric micelles, thus one can expect FA-SMA micelle will follow FR-mediated endocytosis and there will be FR-competition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Luong et al [45] highlighted the synthesis and development of polyvalent theranostic nanocarriers. The construction of this nanoparticle is based on the superparamagnetic iron oxide nanoparticle core (Fe 3 O 4 ) decorated with a FA-G4 PAMAM dendrimer surface that encapsulates the highly potent hydrophobic anticancer agent 3,4-difluorobenzylidene-curcumin.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Targeted chemotherapy, such as intraperitoneal implantable treatment, provides targeted therapy within the peritoneal cavity ( Figure 1) [21][22][23][24][25]. In addition, the preparation of nanoformulations functionalized with specific ligands facilitates preferential targeting of OC tumours and ultimately increases the therapeutic effect in comparison to nonfunctionalized nanosystems [25][26][27][28][29][30]. Table 1.…”
Section: Current Nano-based Drug Delivery Approaches For Ovarian Cancmentioning
confidence: 99%
“…Various prospective biomarkers of OC are reported. Epithelial ovarian tumours display modified cell antigens including, Human Epididymis Protein 4 (HE4 gene), Cancer Antigen 72-4(CA 72-4), Renal Estimated Glomerular Filtration Rate (EGFR), Soluble Mesothelin-Related Peptides (SMRP), Mesothelin, Osteopontin (OPN), Alpha-Fetoprotein (AFP), Cytotoxic T-Lymphocyte-associated Protein 4 (CTLA4), Interferon-alpha (IFNα), Kallikrein-6 (KLK6), phospholipase A2 group 2A (PLA2G2A), Erythroblastic Oncogene B2 (ErbB2), Interleukin-10 (IL-10) and Mucin-16 (MUC1-16), that differentiate cancerous cells from healthy ovarian tissue and other ordinary cells covering the intraperitoneum [23][24][25][26][27][28][29][30]. Mucin proteins (specifically MUC16) show prospective as biomarkers and antibody functionalized micelles to provide a broad range of prospects for OC therapy [32].…”
Section: Current Nano-based Drug Delivery Approaches For Ovarian Cancmentioning
confidence: 99%